2022
DOI: 10.3390/vaccines10030366
|View full text |Cite
|
Sign up to set email alerts
|

Reported Adverse Effects and Attitudes among Arab Populations Following COVID-19 Vaccination: A Large-Scale Multinational Study Implementing Machine Learning Tools in Predicting Post-Vaccination Adverse Effects Based on Predisposing Factors

Abstract: Background: The unprecedented global spread of coronavirus disease 2019 (COVID-19) has imposed huge challenges on the healthcare facilities, and impacted every aspect of life. This has led to the development of several vaccines against COVID-19 within one year. This study aimed to assess the attitudes and the side effects among Arab communities after receiving a COVID-19 vaccine and use of machine learning (ML) tools to predict post-vaccination side effects based on predisposing factors. Methods: An online-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 146 publications
(169 reference statements)
7
33
1
Order By: Relevance
“…The history of infection with COVID-19 increased significantly the risk of developing side effects even in both vaccine groups. The same results were found in multiple previous studies for different COVID-19 vaccines, including the mRNA-based ones ( 23 , 24 , 27 , 28 , 50 , 57 ). Moreover, the antibody titer after COVD-19 vaccination was higher among individuals with a past history of SARS-CoV-2 infection than those who had not been in contact with this pathogen ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The history of infection with COVID-19 increased significantly the risk of developing side effects even in both vaccine groups. The same results were found in multiple previous studies for different COVID-19 vaccines, including the mRNA-based ones ( 23 , 24 , 27 , 28 , 50 , 57 ). Moreover, the antibody titer after COVD-19 vaccination was higher among individuals with a past history of SARS-CoV-2 infection than those who had not been in contact with this pathogen ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, these side effects emerged generally with low frequencies than previously reported, especially with the adenoviral vector vaccines, i.e., AZD1222 where injection site pain was reported with a prevalence higher than 58% ( 24 , 27 , 47 49 ). Similarly, a large-scale multinational study covering more than 10,000 vaccinees in the Arab countries reported that more than 58% of the participants suffered from injection site pain and swelling ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported side effect among the studied HCWs who received the three types of vaccines was fatigue. Many Egyptian, large-scale Arab world and global studies concluded that fatigue was one of the most prevalent s observed following COVID-19 vaccination [ 4 , 22 , 28 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them are non-life threatening, with most cases being mild to moderate in intensity and resolving in a few days. Good knowledge of vaccinations and their adverse effects was substantially related to the vaccination acceptance rate [ 44 ]. As a result, contradicting the rumors, misconceptions, and conspiracy theories regarding COVID-19 vaccinations and their real adverse effects could boost public trust and confidence in COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these factors may also be applicable to understanding COVID-19 vaccination intention. Indeed, it has been reported that positive attitudes toward the vaccine against COVID-19, such as high levels of perceived efficacy and benefits of the vaccine, had a positive association with COVID-19 vaccine acceptance ( Detoc et al, 2020 ; Faasse and Newby, 2020 ; Graffigna et al, 2020 ; Neumann-Böhme et al, 2020 ; Wang et al, 2020 ; Wong et al, 2020 ; Guidry et al, 2021 ; Kateeb et al, 2021 ; Riad et al, 2021b ), while pessimism about side effects, vaccine efficacy and safety have been reported to increase COVID-19 vaccine hesitancy ( Machida et al, 2021 ; Mo et al, 2021a ; Skjefte et al, 2021 ; Hatmal et al, 2022 ). However, all these studies are cross-sectional.…”
Section: Introductionmentioning
confidence: 99%